Efficacy and safety of clopidogrel, ticagrelor, and prasugrel in an all-comers population of patients with ST-segment elevation myocardial infarction. (25th November 2020) - Ravn Jacobsen, M; Engstroem, T; Torp-Pedersen, C; Gislason, G; Glinge, C; Holmvang, L; Pedersen, F; Koeber, L; Jabbari, R; Soerensen, R
Abstract: Background: Until 2009, aspirin and clopidogrel were recommended for most patients with acute coronary syndrome (ACS). After 2009, this recommendation was changed to aspirin combined with prasugrel or ticagrelor since randomised trials had demonstrated reduced cardiovascular mortality and ischemic events, however with a slight increase in bleeding risk. Randomised clinical trials often include selected patients and the results may not be generalisable to an all-comers population of high-risk ACS patients. Purpose: To compare efficacy and safety of clopidogrel, ticagrelor, and prasugrel in all-comers patients with ST-segment elevation myocardial infarction (STEMI). Methods: The Eastern Danish Heart Registry was utilised to identify all consecutive STEMI patients admitted to the capital region from 2009–2016. By individual linkage to Danish nationwide registries, claimed drug prescriptions and end points were obtained. Patients alive a week after discharge were included and stratified according to clopidogrel, ticagrelor, or prasugrel treatment, and followed for 18 months. The risk of the primary efficacy end point (a composite of all-cause mortality, recurrent myocardial infarction, and ischemic stroke) and the safety end point (bleeding events leading to hospital admission) were assessed by multivariate Cox proportional-hazard models. Results: In total, 4841 STEMI patients were included (clopidogrel [n=1222], ticagrelor [n=1820], prasugrel [n=1799]). The median age was 66 (IQR 57–76) for clopidogrel, 64 (IQR 54–73) for ticagrelor, and 59 (IQR 51–67) for prasugrel, and only 19% were women of the prasugrel treated patients (29% for clopidogrel, 25% for ticagrelor). Treatment with anticoagulant therapy was 21% for clopidogrel treated patients (4% for ticagrelor, 5% for prasugrel). Number of events and incidence rates/100 years (IR) for the primary efficacy end point were 165 (IR 9.7) for clopidogrel, 134 (IR 5.1) for ticagrelor, and 107 (IR 4.1) for prasugrel, and for bleeding events 57 (IR 3.3) for clopidogrel, 60 (IR 2.3) for ticagrelor, and 55 (IR 2.1) for prasugrel treatment. Compared with clopidogrel, a reduction in the primary efficacy end point was found in patients treated with both ticagrelor (HR 0.47, 95% CI 0.36–0.63, p<0.001) and prasugrel (HR 0.49, 95% CI 0.36–0.67, p<0.001) with no difference in bleeding events (HR 0.71, 95% CI 0.45–1.13, p=0.15 and HR 0.72, 95% CI 0.44–1.17, p=0.18, respectively). No differences were found between prasugrel and ticagrelor treated patients for the primary efficacy end point (HR 0.83, 95% CI 0.60–1.16, p=0.28) or safety end point (HR 0.97, 95% CI 0.61–1.54, p=0.90). Conclusion: Ticagrelor and prasugrel treatment in all-comers STEMI patients were associated with reduced rates of all-cause mortality and ischemic events without an increase in bleeding events when compared with clopidogrel treatment. No differences in efficacy or safety were found between prasugrel and ticagrelor treated patients. Funding Acknowledgement: Type of funding source: None